Relative length as a classification parameter of the crystallization mode of amorphous films - Bagmut, A.G. (Вопросы атомной науки и техники, 2022)
The possibility of using of the relative length δ₀ as a parameter, determining the polymorphous crystallization mode of amorphous films, was considered. Following polymorphous crystallization modes have been identified based on the structural and morphological characteristics. Layer polymorphous crystallization mode, describes the nucleation and growth of a single-crystal layer in the field of the electron-beam impact, for which δ₀ is about several thousand (3000…5000). Island polymorphous crystallization mode, describes the nucleation and growth of a polycrystalline layer, for which δ₀ is about several hundred (100…1100). Dendrite polymorphous crystallization mode, describes the nucleation and growth of dendrite, for which δ₀ is about several thousand (∼ 4000). Розглянуто можливість використання відносної довжини δ₀ як параметр, що визначає тип поліморфної кристалізації аморфних плівок. Були ідентифіковані наступні типи поліморфної кристалізації на основі структурних і морфологічних характеристик. Це шарова поліморфна кристалізація, яка описує зародження і зростання монокристалічного шару в полі електронно-променевого впливу. Для неї δ₀ становить кількох тисяч (3000…5000). Острівцева поліморфна кристалізація описує зародження і зростання полікристалічного шару. Значення δ₀ становить кількох сотень (100…1100). Дендритна поліморфна кристалізація описує зародження і зростання дендриту. В цьому випадку δ₀ складає кілька тисяч (∼ 4000). Рассмотрена возможность использования относительной длины δ₀ в качестве параметра, определяющего тип полиморфной кристаллизации аморфных пленок. Были идентифицированы следующие типы полиморфной кристаллизации на основе структурных и морфологических характеристик. Слоевая полиморфная кристаллизация описывает зарождение и рост монокристаллического слоя в поле электронно-лучевого воздействия. Для нее δ₀ составляет нескольких тысяч (3000…5000). Островковая полиморфная кристаллизация описывает зарождение и рост поликристаллического слоя. Значение δ₀ составляет несколько сотен (100…1100). Дендритная полиморфная кристаллизация описывает зарождение и рост дендрита. В этом случае δ₀ составляет несколько тысяч (∼ 4000).